2008
DOI: 10.1083/jcb.200801078
|View full text |Cite
|
Sign up to set email alerts
|

ERK5 promotes Src-induced podosome formation by limiting Rho activation

Abstract: Increased Src activity, often associated with tumorigenesis, leads to the formation of invasive adhesions termed podosomes. Podosome formation requires the function of Rho family guanosine triphosphatases and reorganization of the actin cytoskeleton. In addition, Src induces changes in gene expression required for transformation, in part by activating mitogen-activated protein kinase (MAPK) signaling pathways. We sought to determine whether MAPK signaling regulates podosome formation. Unlike extracellular sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 64 publications
3
40
0
Order By: Relevance
“…English and coworkers suggested that Ras could regulate ERK5 activity (English et al, 1999) and Kamakura and coworkers proposed that Ras was important in EGF activation of ERK5 (Kamakura et al, 1999), in direct contrast to an earlier study investigating EGF activation of ERK5 (Kato et al, 1998). The non-receptor tyrosine kinase, Src, activates ERK5 (Schramp et al, 2008) and Src has been proposed as an intermediate in EGF stimulation of ERK5 activity (Sun et al, 2003). Recent studies investigating ERK5 as a downstream target of brain-derived neurotrophic factor (BDNF) activity (Wang et al, 2006b) have identified a Rap1-MEKK2 signalling cascade that activates ERK5; Ras and MEKK3 did not have a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…English and coworkers suggested that Ras could regulate ERK5 activity (English et al, 1999) and Kamakura and coworkers proposed that Ras was important in EGF activation of ERK5 (Kamakura et al, 1999), in direct contrast to an earlier study investigating EGF activation of ERK5 (Kato et al, 1998). The non-receptor tyrosine kinase, Src, activates ERK5 (Schramp et al, 2008) and Src has been proposed as an intermediate in EGF stimulation of ERK5 activity (Sun et al, 2003). Recent studies investigating ERK5 as a downstream target of brain-derived neurotrophic factor (BDNF) activity (Wang et al, 2006b) have identified a Rap1-MEKK2 signalling cascade that activates ERK5; Ras and MEKK3 did not have a significant role.…”
Section: Discussionmentioning
confidence: 99%
“…36,37 In addition, the blockade of RhoA signaling significantly increased podosome formation in myeKlf5 −/− macrophages, suggesting KLF5-independnet podosome formation. Indeed, Mark Schramp et al 38 reported that ERK5 promotes Src-induced podosome formation in Src-transformed fibroblasts by limiting Rho activation. Pathways through which KLF5 modulates Rho activity, podosome formation, and cellular invasion are of considerable interest.…”
Section: Discussionmentioning
confidence: 99%
“…The phosphorylation of p190RhoGAP has a direct effect on RhoA activity and increases the hydrolysis rate of GTP-bound RhoA, resulting in a smaller pool of activated RhoA (1,6,49), as observed in the Sam68 Ϫ/Ϫ MEFs. RhoA inactivation is not always observed with Src activation, as v-Src-transformed cells maintain elevated levels of active RhoA (4,69). Moreover, Src has been shown to regulate Rho GTPase activity by Rho GDP dissociation inhibitor (RhoGDI) phosphorylation and by decreasing the association of RhoGDI with Rho GTPases (19).…”
Section: Discussionmentioning
confidence: 99%